A prospective analysis of symptom burden for patients with chronic myeloid leukemia in chronic phase treated with frontline second‐ and third‐generation tyrosine kinase inhibitors. (14th October 2018) - Zulbaran‐Rojas, Alejandro; Lin, Huei‐Kan; Shi, Qiuling; Williams, Loretta A.; George, Binsah; Garcia‐Manero, Guillermo; Jabbour, Elias; O'Brien, Susan; Ravandi, Farhad; Wierda, William; Estrov, Zeev; Borthakur, Gautam; et al.
Abstract: Background: Treatment with tyrosine kinase inhibitors (TKIs) for patients with chronic myeloid leukemia (CML) is effective but needs to continue for several years, possibly indefinitely. Although generally safe, TKI may have hitherto poorly recognized effects in the quality of life (QoL) of such patients. Methods: We prospectively measured the symptom burden of patients with chronic phase CML enrolled on frontline TKI trials with dasatinib, nilotinib, or ponatinib. A total of 219 patients were enrolled and filled out the MD Anderson Symptom Inventory (MDASI)‐CML questionnaire before the start of therapy and during follow‐up at defined time points of 3, 6, 9, 12, 18, and 24 months. Results: The median age was 50 years. Longitudinal analysis showed relatively stable symptom severity scores over time. Fatigue was the most common symptom in all three cohorts, both prior to the start of therapy and during therapy, including after achievement of deep molecular remission. Work was the most affected component of daily living. Overall patients tolerated therapy well with improvement of their symptoms from baseline, with few dose reductions related to toxicity or symptomatology. Although 31% of the patients who completed MDASI‐CML achieved complete molecular remission by 24 months of treatment, nearly 90% experienced persistent mild symptoms. Conclusion: Side effects related to TKIs may impact the quality of life in patients with CML‐CP. Further studies should investigate factors (comorbidities, concomitant medications, dose and schedule, etc) associated with these symptoms and interventions that may improve the patients' QoL, including treatment discontinuation when safely feasible. Abstract : We prospectively measured the symptom burden of 219 patients with chronic phase chronic myeloid leukemia (CML‐CP) enrolled on frontline tyrosine kinase inhibitor (TKI) trials with dasatinib, nilotinib, or ponatinib using a previously validated questionnaire. Overall, patients tolerated therapy well with improvement of their symptoms from baseline, with few dose reductions related to toxicity or symptomatology, and nearly 90% experienced persistent mild symptoms. Side effects related to TKIs may impact the quality of life in patients with CML‐CP.